Specific amino acids but not total protein attenuate postpartum weight gain among Hispanic women from Southern California. Issue 4 (13th February 2021) - Wild, Laura E.; Alderete, Tanya L.; Naik, Noopur C.; Patterson, William B.; Berger, Paige K.; Jones, Roshonda B.; Plows, Jasmine F.; Goran, Michael I.
Abstract: There is a high prevalence of obesity and type 2 diabetes in the United States, particularly among Hispanic women, which may be partly explained by failure to lose gestational weight during the postpartum period. Previous work indicates that protein and amino acids may protect against weight gain; therefore, this study examined the impact of dietary protein and amino acid intake on changes in postpartum weight and the percent of women meeting the Estimated Average Requirement (EAR) for these dietary variables among Hispanic women from the Southern California Mother's Milk Study ( n  = 99). Multivariable linear regression analysis was used to examine the associations between protein and amino acid intake with change in weight after adjusting for maternal age, height, and energy intake. Women's weight increased from prepregnancy to 1‐month and 6‐months postpartum (71.1 ± 14.6 vs. 73.1 ± 13.1 vs. 74.5 ± 14.6 kg, p  < .0001). Although dietary protein was not associated with weight change ( β  = −1.09; p  = .13), phenylalanine ( β  = −1.46; p  = .04), tryptophan ( β  = −1.71; p  = .009), valine ( β  = −1.34; p  = .04), isoleucine ( β  = −1.26; p  = .045), and cysteine ( β  = −1.52; p  = .02) intake were inversely associated with weight change. Additionally, fewer women met the EAR values for cysteine (11.1%), phenylalanine (60.6%), and methionine (69.7%), whereas most women met the EAR values for tryptophan (92.9%), valine (96.0%), and isoleucine (94.9%). Study results indicate that several essential and conditionally essential amino acids were associated with postpartum weight loss, with a significant portion of women not meeting recommended intake levels for some of these amino acids. These results highlight the importance of postpartum maternal diet as a potential modifiable risk factor. Abstract : Among 99 Hispanic women from the Southern California Mother's Milk Study, dietary protein was not associated with postpartum weight change; however, several amino acids (i.e., phenylalanine, tryptophan, valine, isoleucine, and cysteine) were inversely associated with change in weight from 1‐ to 6‐months postpartum. Additionally, less than 50% of women were consuming the recommended amounts of dietary protein, tyrosine, and cysteine. These results suggest that dietary protein and amino acids should be considered when developing obesity prevention strategies for Hispanic women during the postpartum period.